2014
DOI: 10.3892/etm.2014.1821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of artemin and GFRα1 expression in laryngeal squamous cell carcinoma

Abstract: Artemin (ARTN) has been implicated in the development and progression of several human malignancies. However, the clinical and prognostic significance of ARTN and its receptors has not yet been investigated in human laryngeal squamous cell carcinoma (LSCC). Therefore, in the present study, the protein expression of ARTN and its receptor, namely GFRα1, was determined in 76 LSCC and 26 laryngeal polyp tissue samples using immunohistochemistry. Furthermore, the clinicopathological and prognostic significance of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Artemin, a member of the GDNF family, is overexpressed in human laryngeal SCC and is associated with poor survival and high tumor stage (Gao et al 2014). In pancreatic cancer cell lines, artemin enhances neurotropic invasion (Gao et al 2015), but the association between artemin and PNI has not been investigated in SCC.…”
Section: Molecular Markers and Regulationmentioning
confidence: 99%
“…Artemin, a member of the GDNF family, is overexpressed in human laryngeal SCC and is associated with poor survival and high tumor stage (Gao et al 2014). In pancreatic cancer cell lines, artemin enhances neurotropic invasion (Gao et al 2015), but the association between artemin and PNI has not been investigated in SCC.…”
Section: Molecular Markers and Regulationmentioning
confidence: 99%
“…In addition positive GDNF expression was associated with increased perineural invasion, lymphatic metastasis and decreased overall survival of patients [26]. In laryngeal squamous cell carcinoma, the expression of GFRα1 and ARTN, another GFL member, was associated with more advanced pTNM stage [19]. GFL member PSPN has been suggested to play a key role in human oral cancer progression [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, GDNF and its related family members have been shown to enhance tumor aggressiveness by increasing tumor cell migration [15][16][17] and promoting perineural invasion [18]. In laryngeal carcinoma, a type of HNSCC, higher expression of GFRα1 and ARTN was associated with more advanced pTNM stage [19]. The expression of another GFL member, PSPN, was also noted to be higher in primary oral squamous cell carcinoma compared to normal mucosa [20].…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances have been made in miRNA-based therapy; however, many challenges must be overcome before clinical usage [ 89 ]. Regardless, several studies reported miR-223 expression as a potential diagnostic and therapeutic target [ 36 , 89 , 90 , 91 ].…”
Section: Mir-223 Application As a Diagnostic And Therapeutic Biomarke...mentioning
confidence: 99%
“…Most physicians recommend surgical resection for esophageal carcinomas at their early stages [ 98 ]. Due to the limited treatment options, further research is needed to identify biomolecular pathways involved in esophageal cancer malignancy [ 90 , 98 , 99 ].…”
Section: Mir-223 Application As a Diagnostic And Therapeutic Biomarke...mentioning
confidence: 99%